Pengaruh Kepemimpinan Digital Dan Knowledge Sharing Terhadap Kinerja Pegawai Melalui Perilaku Kerja Inovatif Pada Kantor Unit Penyelenggara Pelabuhan Kelas Ii Maccini Baji Kabupaten Pangkajene Dan Kepulauan - Arifin, Ince Arydha Illahi; Indira Basalamah; Masriadi Patu (Jurnal Ilmiah Neraca : Ekonomi Bisnis, Manajemen, Akuntansi, 2025)
The purpose of this study was to examine the influence of: (1) digital leadership on innovative work behavior. (2) knowledge sharing on innovative work behavior. (3) digital leadership on employee performance. (4) knowledge sharing influences employee performance. (5) innovative work behavior influences employee performance. (6) digital leadership influences employee performance through innovative work behavior. (7) knowledge sharing influences employee performance through innovative work behavior. The research location was the Maccini Baji Class II Port Management Unit Office in Pangkajene and Kepulauan Regency. The population was 128 employees. Data collection used a questionnaire. The sampling method was saturated sampling. The analysis method used SEM-PLS. The results of the study are as follows: (1) digital leadership has a positive but insignificant effect on innovative work behavior. (2) knowledge sharing has a positive and significant effect on innovative work behavior. (3) digital leadership has a positive and significant effect on employee performance. (4) knowledge sharing has a positive and significant effect on employee performance. (5) innovative work behavior has a positive but insignificant effect on employee performance. (6) digital leadership has a positive and significant effect on employee performance through innovative work behavior. (7) Knowledge sharing has a positive and significant impact on employee performance through innovative work behavior. Keywords: Digital Leadership; Knowledge Sharing; Innovative Work Behavior; Employee Performance .